An immunofluorescence microscopy assay to discriminate distinct expression patterns of HIV-1 Gag and Nef proteins in HIV-1 provirus-harboring cells - Rosana Wiscovitch-Russo; Hongyan Sui; Mindy Smith; Hiromi Imamichi; H Clifford Lane; Tomozumi Imamichi (PLoS ONE, 2026)
Over 95% of HIV-1 proviruses are defective and were once considered clinically irrelevant. However, growing evidence shows that these defective proviruses can still be transcribed and translated into viral proteins. Here, we developed an improved immunofluorescence protocol that combines two anti-Nef antibodies with one anti-Gag antibody, along with membrane and nuclear staining, enabling direct visualization of protein expression and localization. This method allows detailed characterization of the expression patterns and subcellular distribution of Gag and Nef proteins derived from defective proviruses. The protocol provides a practical tool for investigating the potential functions of proteins expressed from defective HIV-1 proviruses and for facilitating the ability to determine the biologic activity of cells harboring defective HIV-1 proviruses in patients living with HIV.